2015
DOI: 10.1177/0969733015614882
|View full text |Cite
|
Sign up to set email alerts
|

Drugs down the drain: When nurses object

Abstract: The authors examine the nursing practice of disposing unaltered controlled substances into public water systems as an issue for nurses concerned with the environmental harm it can cause. A summary of the history of controlled substance management reveals inconsistencies in the interpretation of current regulations that have led to disposal policies that vary by institution, according to a benchmarking survey of regional hospitals. Much attention has been given to the phenomenon of conscientious objection in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Additionally, the FDA [9] released a list of medications, which contains primarily opioid medications, that should be "flushed down the toilet as soon as they are no longer needed" if a take-back program is "not readily available." There may be reluctance to flush unused medications due to previous widespread communication that pharmaceuticals (e.g., estrogens and antibiotics) negatively impact the aquatic environment [10][11][12][13][14][15][16]. However, different classes of pharmaceuticals pose varying levels of risk to humans and ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the FDA [9] released a list of medications, which contains primarily opioid medications, that should be "flushed down the toilet as soon as they are no longer needed" if a take-back program is "not readily available." There may be reluctance to flush unused medications due to previous widespread communication that pharmaceuticals (e.g., estrogens and antibiotics) negatively impact the aquatic environment [10][11][12][13][14][15][16]. However, different classes of pharmaceuticals pose varying levels of risk to humans and ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are encouraged to critically examine their own practices to discover activities that could be done differently. For example, nurses identified that the disposal of controlled substances into the sewer system was harmful to the environment and are now working to change these practices (King & McCue, 2017). Nurses can develop and lead ‘green teams’, which are responsible for examining hospital‐wide practices, identifying those that are harmful to the environment, and offering alternatives (Huffling & Schenk, 2014; Lilienfeld et al, 2018; Sayre et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While concern about this practice has been raised with respect to numerous pharmaceutical products, even to the extent that specific protocols for the disposal of certain non-controlled drugs have been issued, controlled substances are often still sewered. Nurses and other hospital staff members tasked with such disposal have raised concern and even conscientious objection to the practice of letting controlled substances enter the wastewater system [ 23 ]. In a survey of hospice home care nurses, 55% said they always or often flushed the unused controlled substances, despite their own doubts about the environmental safety of such practice [ 24 ].…”
Section: Reviewmentioning
confidence: 99%